REE Comparison Between Muncung Granite Samples and their Weathering Products, Lingga Regency, Riau Islands - Irzon, Ronaldo; Syafri, Ildrem; Hutabarat, Johannes; Sendjaja, Purnama (Indonesian Journal on Geoscience, 2016)
DOI:10.17014/ijog.3.3.149-161The increasing demand for Rare Earth Elements (REE) is related to the continous development of technology, and these elements are used in modern equipments. REE can occur in igneous and sedimentary rocks in significant amounts as primary deposits, whereas the secondary REE deposit can be produced by intensive lateritic weathering of bedrocks under the tropical or subtropical climate. Lateritic process can increase REE concentration from sub-economic levels in host rocks to be more valuable. Muncung Granite is located in a tropical area of Lingga Regency, Riau Islands Province. REE occurs in the Muncung Granite and in weathered layers (saprolite, laterite, and soil). ICP-MS was applied to measure the REE content in all samples of this study. The average REE content of the Muncung Granite is 265 ppm with Eu anomaly in REE’s spider diagrams. Lateritization process has increased REE content by more than four times compared to that in the Muncung Granite. Ce and Eu anomalies in weathered layers can be associated with weathering process and initial REE contents in the host rock. Ce anomaly in a laterite layer is found to have a negative correlation to REE total enrichment. The REE level in the Muncung Granite is higher than the content in the soil and saprolite layers, but lower than that in the laterite.